Integrating Vernacular Architectural Elements Into Contemporary Omani Residential Design: A Comparative Analysis of Traditional and Modern Façades - Shahbazzadeh, Afsaneh; Sameh, Reza; Benkari, Naima (Journal of Islamic Architecture, 2025)
This research explores the ways of integrating traditional Omani vernacular architectural elements into contemporary façade designs. It examines how these patterns are reinterpreted to create a consistent architectural language that imbibes local heritage patterns while meeting modern needs. The study investigates the structural, cultural, and formal characteristics of Omani façades through a qualitative analysis of the façades’ components in residential buildings. To identify common patterns and design rules in contemporary Omani architecture, a comparative approach was employed to analyze 24 residential buildings in Mirbat and Mutrah. The results show that vernacular elements are continuously reinterpreted in modern design, revealing that these patterns not only maintain cultural identity but also enhance the practicality of contemporary architecture. Finally, the investigation proposes a guideline for incorporating heritage elements within current design agendas, catalyzing further dialogue on architectural identity in the Islamic world.